KEDUDUKAN DAN HAK MEWARIS ISTERI DARI PERKAWINAN SECARA ADAT PASU-PASU RAJA DI KECAMATAN LUMBAN JULU KABUPATEN TOBA SAMOSIR - ROSMERI ROSMERI (PREMISE LAW JURNAL, 2017)
Batak Toba community is never separated from their adat (customary) rules in their daily life, and one of them is a marriage. In the Batak Toba community, ‘Pasu-Pasu Raja’ marriage is a marriage between a man and a woman by receiving blessing from ‘raja-raja ni huta’, the men who are considered as the old in a village, adat leaders, and the representatives of families of the bride and the groom. The research used descriptive analytic and judicial empirical method. The position of a wife in ‘Pasu-Pasu Raja’ marriage is very weak by law because it is not recognized by the Church and the State. Her right in inheritance will be considered according to the adat (customary) rules and the decision of the community. Her legal remedy is by asking help from the adat community and by registering the marriage to the Church by confessing her guilt and by willing to change so that the ‘Pasu-Pasu Raja’ marriage will be legally legitimate and her rights can be protected when there is a divorce and death. Keywords: Position, Right in Inheritance, Wife, Pasu-Pasu Raja Marriage